Piecing the evidences: Barriers to utilization of Antenatal Care Services by Currently Married Women in Rural Uttarakhand- A community-based study - Juyal, Ruchi; Semwal, Jayanti; Kandpal, Sunil Dutt; Kumar Srivastava, Ashok; Deep Shikha; Vallabh, Vidisha (Indian Journal of Community Health, 2020)
Background: High maternal mortality has always been an area of concern in developing countries. Availability and availment of adequate antenatal care play a significant role in reduction of maternal deaths. Aim & Objective: To know the extent of antenatal care (ANC) services utilization by the currently married women of rural Uttarakhand during their last pregnancy, to find the barriers for utilization of ANC services and correlate the socio-demographic variables with the non-utilization of ANC services. Methods and Material: This correlational study was conducted in rural areas of 3 randomly selected districts in Uttarakhand. Multistage stratified and simple random samplings were used for area selection and PPS technique was used to recruit the participants. Overall, 637 currently married women (CMW) who delivered in last 5 years prior to survey, were interviewed by trained social workers. Chi-square test was used to ascertain association between variables and regression analysis was done to adjust for confounding associations. Results: Overall 496 (77.9%) women availed one or more ANC services during their last pregnancy, but the complete package was availed by only 210 (33%) of the CMW. Majority of the women who did not avail any ANC services were older, illiterate, labourer, spouse of labourer/ unemployed person and belonged to lower socio-economic status. Unawareness was the most commonly cited reason for not availing ANC services followed by financial issues and unfelt need. Conclusions: Women in Uttarakhand are pliant to ANC services, but there is a need to create demand for it by increasing awareness and improving the quality of ANC services.